Faculty development for student achievement : (Anker Pub., 2006)
Contents include: The QUE process at the national and local levels; Evolution of a biologist’s perspective; Chemistry education today; The English chair’s guide to a learning-centered curriculum; The QUE project and history learning and teaching; Mathematics and QUE; Reflections and recommendations